COMPETITIVENESS OF HIGHER EDUCATION INSTITUTIONS IN UKRAINE: EDUCOLOGYCAL ASPECT - Olga Melnychenko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article is devoted to the analysis of the competitiveness of institutions of higher education from the point of view of Educology - an integrated science of education, which is a kind of educational synergy for the study of the field of education. Emphasizing the interdisciplinary nature of educational research, which includes economic, social, legal, cultural, managerial and other aspects, the author characterizes the concept of competition and competitiveness in the field of education in the context of the internationalization of the educational industry, investigates its factors. The article reveals the essence of competition, its functions and driving forces of the educational market, as well as the interrelationship of the influence of the latest trends in the development of education on the competitiveness of higher education institutions. Special attention is paid to the analysis of the concept of «educational services», the main approaches to its definition, the characteristics of the features of the creation of educational services by institutions of higher education, their classification and types of educational services on the educational market, as well as the concept of additional educational services. The author notes that the main task and the main function of competition is the conquest of the educational market, the fight for the consumer, the victory of one's competitors, and the provision of stable profits. In addition, the essence of competition is expressed by certain forces that encourage it to develop, regardless of whether it operates only on the domestic market or on the foreign market as well. The article pays special attention to the characteristics of educational services, which have the following advantages: availability of additional educational services provided by a higher education institution; the possibility of mobile exchange of students and internships for teachers both within the country and abroad; practical significance of training, its practice-oriented content; assistance with employment for graduates of a higher education institution; proper material and technical base, availability of modern information and communication technologies.